The life cycle of contributors in collaborative online communities -the case of OpenStreetMap. Issue 8 (3rd August 2018) - Bégin, Daniel; Devillers, Rodolphe; Roche, Stéphane
ABSTRACT: Over the last two decades, online communities have become ubiquitous, with millions of people accessing collaborative project websites every day. Among them, the OpenStreetMap project (OSM) has been very successful in collecting/offering volunteered geographic information (VGI). Very different behaviours are observed among OSM participants, which translate into large differences of lifespan, contribution levels (e.g. Nielsen's 90–9-1 rule) and attitudes towards innovations (e.g. Diffusion of innovation theory or DoIT). So far, the literature has defined phases in the life cycle of contributors only based on the nature of their contributions (e.g. role of participants and edits characteristics). Our study identifies the different phases of their life cycle from a temporal perspective and assesses how these phases relate to the volume and the frequency of the contributions from participants. Survival analyses were performed using both a complementary cumulative distribution function and a Kaplan-Meier estimator to plot survival and hazard curves. The analyses were broken down according to Nielsen and DoIT contributors' categories to highlight potential explanatory variables. This paper shows that two contribution processes combine with three major participation stages to form six phases in contributors' life cycle. The volume of edits provided on each active day is driven by the two contribution processes, illustrating the evolution of contributors' motivation over time. Since contributors' lifespan is a universal metric, our results may also apply to other collaborative online communities.